Cryopreservation for eradication of Jujube witches' broom phytoplasma from Chinese jujube (Ziziphus jujuba). (3rd December 2014) - Wang, R.R.; Mou, H.Q.; Gao, X.X.; Chen, L.; Li, M.F.; Wang, Q.C.
Abstract Here, we report efficient eradication of Jujube witches' broom phytoplasma (Candidatus Phytoplasma ziziphi) from Chinese jujube (Ziziphus jujuba) by cryopreservation. Shoot tips (1.0 mm in size) with 5–6 leaf primordia (LPs) excised from diseased in vitro stock shoots were subject to droplet‐vitrification cryopreservation. Shoot tips following cryopreservation were post‐cultured on a recovery medium for survival. Plantlet regeneration was obtained by micrografting of surviving shoot tips upon in vitro rootstocks. With this protocol, 85% of shoot tips survived following cryopreservation, among which 75% regenerated into whole plantlets and all of them were free of phytoplasma, regardless of the sizes used for cryopreservation. Ultrastructural studies demonstrated that phytoplasma was absent in the apical dome, and leaf primordia (LPs) 1 and 2, while abundance of phytoplasma was present in the lower parts of shoot tips, leaf primordium 3 and older tissues. Histological observations showed that much more damage was found in cells located in the lower part of apical dome, leaf primordium 3 and older tissues than in those at the upper part of apical dome and in the LPs 1 and 2. These cells were most likely to survive and regenerate into phytoplasma‐free plantlets following cryopreservation and micrografting. Ploidy levels analyzed by flow cytometry (FCM) were maintained in plantlets regenerated from cryopreservation followed by micrografting. Results reported here would provide technical support for production of phytoplasma‐free plants and for long‐term storage of germplasm of Chinese jujube.